INFLUENCE OF GAS THERMAL PROCESS PARAMETERS SPRAYING OF COATINGS FOR THEIR WEAR RESISTANCE AND ADHESION STRENGTH - Lopata, Oleksandr (Problems of Friction and Wear, 2023)
The article presents a comprehensive impact assessment based on experimental research technological parameters of the gas-thermal spraying process (spraying distance), design parameters (coating thickness) and operational parameters (conditions operation - load and sliding speed) on grip strength and intensity wear and tear of gas-thermal coatings. the effect of each of them on the properties was established received coatings. The study of HTN coatings with variation of its main parameters made it possible to assess the influence of each of them on the properties of surfaces with sprayed coatings. On the basis of the obtained experimental results, models have been developed that relate the adhesion strength and wear intensity of the coatings to their thickness and spraying distance. Solving the problems of mathematical modeling and optimization of the HTN coating process makes it possible to obtain a comprehensive assessment of the influence of input variables (HTN process parameters) on the output indicators - the properties of sprayed coatings. Analyzing the obtained models, it should be noted that the adhesion strength of the coatings depends on their thickness and spraying distance. The wear resistance of the coatings is influenced by its operating conditions (load and sliding speed). It was concluded that to increase the adhesion strength of gas thermal coatings and reducing the intensity of their wear is expedient to use comprehensively influence of spraying distance, coating thickness and conditions of its operation.